Direct inhibition of transcription in vitro by the isolated N-terminal domain of the Escherichia coli nucleoid-associated protein H-NS and by its paralogue Hha. Issue 4 (6th February 2019) - Kapshikar, Rajvardhan M.; Gowrishankar, J.
Abstract : H-NS is an abundant nucleoid-associated protein in the enterobacteria that mediates both chromatin compaction and transcriptional silencing of numerous genes, especially those that have been acquired by horizontal transfer or that are involved in virulence functions. With two dimerization domains (N-terminal and central) and a C-terminal DNA-binding domain, the 15 kDa H-NS polypeptide can assemble as long polymeric filaments on DNA, and mutations in any of the three domains confer a dominant-negative phenotype in vivo by a subunit-poisoning mechanism. Here we confirm that several of these mutants [L26P, I119T and a truncation beyond residue 92(Δ93)] are also dominant-negative in vitro, in that they reverse the inhibition imposed by native H-NS in two different transcription assay formats (initiation+elongation, or elongation alone). On the other hand, another dominant-negative truncation mutant Δ64 (which possesses only the protein's N-terminal domain) per se completely and unexpectedly inhibited transcription in both assay formats. The Hha protein, which is a paralogue of H-NS and resembles its isolated N-terminal domain, also behaved like Δ64 as an inhibitor of transcription in vitro. We propose that under certain growth conditions, Escherichia coli RNA polymerase may be the direct inhibitory target of Hha, and that this effect is experimentally mimicked by the isolated N-terminal domain of H-NS.